Evolution of disability pension after renal transplantation: methods and results of a database linkage study of the Swiss Transplant Cohort Study and Swiss Disability Insurance (Swiss Medical Weekly, 2021)
AIMS: In Switzerland, certain patients with disabilities and reduced working ability are entitled to a disability pension granted by the Swiss Federal Social Insurance Office (FSIO). The aim was to assess the evolution of disability pension and work capacity after kidney transplantation and thereby pilot the procedures linking FSIO data with Swiss Transplant Cohort Study (STCS) data.METHODS: The current study pilot tested the record linkage of FSIO data with data from the STCS in a single-centre, observational setting. Patients were requested to consent to the use of their Swiss social security number (SSSN) for the purpose of record linkage. A privacy preserving trust centre approach was implemented with blinded statistical analysis.RESULTS: Between May 2008 and December 2015, 282 working-age renal transplant recipients of the University Hospital of Basel transplant centre were eligible for inclusion and 136 (48%, median age 48 years) consented to the use of their social security number and record linkage. The FSIO datasets of all patients were successfully retrieved and linked to STCS data in the trust centre and were numerically analysable. Yearly FSIO allowance data were available for the entire study duration. Fifty-five patients (40%) were registered as disability insurance recipients (DIR). In the entire population, the proportion of working patients slightly decreased from 76% to 72% between the pre-transplant and the post-transplant period. This was due to the lower proportion of patients working after transplantation in DIR compared with non-recipients (non-DIR) (DIR: 60% before vs 44% after; non-DIR: 83% before vs 88% after). In the DIR group, the proportion of patients not working increased from 36% to 49%, whereas in non-DIR the proportion changed only marginally (14% to 12%). The average disability insurance allowance was CHF 1172 per month. It changed from CHF 1135 before transplantation to CHF 1209 after transplantation (p = 0.59).CONCLUSIONS: In the Swiss healthcare and social insurance system, record linkage studies combining clinical datasets with data from FSIO are feasible but associated with great efforts and resource needs. The lack of changes in disability allowances after kidney transplantation should be further investigated in the nationwide setting.ClinicalTrials.gov Number: NCT01204944